2017
DOI: 10.3389/fmicb.2017.00795
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Analysis of Mycobacterium tuberculosis Lineage 7 and Lineage 4 Strains Reveals Differentially Abundant Proteins Linked to Slow Growth and Virulence

Abstract: In order to decipher the nature of the slowly growing Mycobacterium tuberculosis (M.tuberculosis) lineage 7, the differentially abundant proteins in strains of M. tuberculosis lineage 7 and lineage 4 were defined. Comparative proteomic analysis by mass spectrometry was employed to identify, quantitate and compare the protein profiles of strains from the two M. tuberculosis lineages. Label-free peptide quantification of whole cells from M. tuberculosis lineage 7 and 4 yielded the identification of 2825 and 2541… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
2
27
0
Order By: Relevance
“…The ppe37 genes of M. tuberculosis, virulent M. bovis, and BCG are all transcribed at relatively low levels (when not induced by low iron), but PPE37 is often not detected by proteomics methods even with high coverage of the theoretical proteome, likely due to low expression and the general difficulty in detecting acidic PE/PPE proteins (45)(46)(47)(48)(49). However, one study which achieved 87% coverage of the BCG proteome by separately analyzing cell wall, plasma membrane, and cytoplasm fractions identified PPE37, indicating that the protein is expressed by BCG (50).…”
Section: Figmentioning
confidence: 99%
“…The ppe37 genes of M. tuberculosis, virulent M. bovis, and BCG are all transcribed at relatively low levels (when not induced by low iron), but PPE37 is often not detected by proteomics methods even with high coverage of the theoretical proteome, likely due to low expression and the general difficulty in detecting acidic PE/PPE proteins (45)(46)(47)(48)(49). However, one study which achieved 87% coverage of the BCG proteome by separately analyzing cell wall, plasma membrane, and cytoplasm fractions identified PPE37, indicating that the protein is expressed by BCG (50).…”
Section: Figmentioning
confidence: 99%
“…Understanding the molecular epidemiology of TB is important for regional disease control. For instance, distinct strains may be linked to outbreaks [10], high virulence [42], emergency of drug resistance [44], disease progression [43], and can point to the geographic origin of a strain [20,33] as well as identify new lineages [17,28].…”
Section: Introductionmentioning
confidence: 99%
“…Lineage 7 is a recently identified lineage of Mtb, characterized by slow-growth and reduced virulence phenotypes. 100,101 The GO enrichment analysis of 161 proteins hypoacetylated in lineage 7 revealed that pathogenesis, growth, glycolysis, response to iron ion, response to nitrosative stress, and protein folding were among the significantly enriched biological processes (Figure 7A,B). Carbon metabolism, TCA cycle, oxidative phosphorylation, and microbial metabolism in diverse environments were some of the significantly enriched pathways from these hypoacetylated proteins (Figure 7B, Table S6-2).…”
Section: Resultsmentioning
confidence: 99%